TUJUAN PENCIPTAAN MANUSIA DAN FUNGSI LEMBAGA-LEMBAGA PENDIDIKAN - Hasan, Muhammad (State Institute of Islamic Studies (IAIN) Palu, 2010)
God created all His creatures based on His might. He created human beings in the best form with combinationÂ Â of physics, reason, and spirituality. The experts in education have a concensus that to organize the civilization of human beings, education mustÂ be based on the proporrtional education demenstions, namely the balance between the physics and the spituality.Kata Kunci: penciptaan manusia, fungsi lembaga pendidikan